The mechanism of bedding separation in roof strata overlying a roadway within a thick coal seam: A case study from the Pingshuo Coalfield, China. (April 2016) - Yan, Hong; He, Fulian; Yang, Tao; Li, Linyue; Zhang, Shoubao; Zhang, Jixiong
Abstract: Bedding separation in roof strata (BSRS) overlying roadways within thick coal seams (RTCS) is an important factor leading to surrounding instability in underground coal mines, and especially to roof failures such as convergence, and even caving-in. To prevent reason, and to protect the working miners, it is essential to understand the mechanism of underpinning BSRS overlying RTCS. In this research, combined with the theoretical analysis and test results of continuous, and discontinuous, beams and stratified rock strata load, a new approach to predict the locations at which BSRS occurred was proposed; additionally, the calculation equation for BSRS was deduced. Based on standard monitoring methods widely used in exploring roof behaviour in underground coal roadways, a typical roadway excavated within 12.87 m, in an average thickness coal seam, in Jinggonger coal mine, Pingshuo Coalfield, Shanxi Province, China, that was chosen to explore the mechanism underpinning BSRS, and a set of monitoring designs, mainly including five groups of stations and 16 instruments, is determined and applied to this research. Results showed that the predicted locations of BSRS overlying RTCS were in accordance with field monitoring results. This proved the validity of the theoretical model. Besides, the working face played an important role in BSRS and 75% of the BSRS events were generated within the 50 m between the monitoring station and the working face. When the distance was decreased to 5 m, the BSRS was up to 90.9 mm and 86 mm at depths of 6.8 m and 3.8 m, respectively. Meanwhile, three stages were considered, step-by-step, as opposed to mining activity dependent upon the extent of its influence on BSRS: a pink value (indicative of an alarm status) prevailed during the third stage. Highlights: A mathematical model was proposed for predicting the BSRS locations in roadways within thick coal seam. The online monitoring system was employed in exploring coal/rock behaviour above coal roadways. The mechanism discovering BSRS was claimed according to the theoretical analysis and monitored results.